Distribution of Ferns at Different Heights in Gunung Raya Protected Forest, West Kalimantan - Natasya, Dea Fitri; Daningsih, Entin; Yuniarti, Anisyah (Biotik, 2024)
Abstract: Ferns are a type of biodiversity that is spread to live on the forest floor and plays an important role in ecological functions, such as humus formation, protecting soil from erosion, and maintaining soil moisture. This study aims to determine the distribution of fern species at different heights in the Gunung Raya Protection Forest, Temajuk Village and their potential for the community. The method in this study, namely the cruising method to observe ferns on soil contours with an altitude of 25-125 meters above sea level, 125-225 meters above sea level, and 225-325 meters above sea level. Environmental parameters including temperature, humidity, light intensity, soil pH and wind speed were measured at each altitude.  Herbarium was made to identify ferns. Information about the potential of ferns was obtained from the surrounding community. The results showed that there were 14 species of ferns belonging to 7 families. Ferns found were as many as 14 species at an altitude of 25-225 masl decreased to 10 species at the highest contour (325 masl). The four species that were not found were Stenochlaena palustris, Nephrolepis cordifolia, Hypolepis punctata, and Davalia divaricata. Of the 14 species of ferns, 11 of them have potential as vegetables, medicines, ornamental plants, and craft materials.